Charcot Neuroarthropathy Confused with Venous Insufficiency in a Diabetic Patient - Rabia Terzi; Tülay Özer; Turgay Altınbilek (Galenos Yayinevi, 2017)
Charcot neuroarthropathy (CN) is a disease with a progressive course which usually affects the foot and ankle and can be seen with all the diseases causing sensory or autonomic neuropathy, primarily diabetes. Diagnosis can be delayed since it may be confused with many clinical entities, particularly infections and vascular pathologies which are seen especially in the course of diabetes. In this case report a 59 year-old diabetic patient, who presented with swelling and pain in the right foot, was previously diagnosed with venous insufficiency and then found to have CN, was presented together with a literature review.